M.N. Srinivas and sociology - Panini, M.N. (2000)
Sociologists, M.N. Srinivas believed, should recognise that they deal with `messy' phenomena and all they can do is to muddle through to discern patterns wherever possible. In doing so often the sociologist has to be like a craftsman who makes his own tools to handle his material. The sociologist has to either improvise concepts or borrow appropriate ones to gain insights into significant processes and arrange messy data to uncover patterns and structures they hide. - Reproduced
Keywords: Sociologists; Srinivas, M.N.